2006
DOI: 10.1111/j.1945-5100.2006.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of minerals and meteoritic materials via Raman techniques after capture in hypervelocity impacts on aerogel

Abstract: Abstract-Mineral particles analogous to components of cosmic dust were tested to determine if their Raman signatures can be recognized after hypervelocity capture in aerogel. The mineral particles were accelerated onto the silica aerogel by light-gas-gun shots. It was found that all the individual minerals captured in aerogel could be identified using Raman (or fluorescence) spectra. The laser beam spot size was ∼5 micrometers, and in some cases the captured particles were of a similar small size. In some samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…(2001) for olivine and enstatite. Subsequent work showed that a wide range of minerals could be identified with grain sizes down to 5 μm (Burchell et al. 2006b).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…(2001) for olivine and enstatite. Subsequent work showed that a wide range of minerals could be identified with grain sizes down to 5 μm (Burchell et al. 2006b).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Therefore, a spectrum acquired in the carbon first-order region only revealing one broad band at 1320 D cm -1 should not be assigned to carbon. Hematite and sp 2 carbonaceous materials can co-occur as mixed opaque phases in sediments, rocks, and meteorites (e.g., Burchell et al, 2006;Mahaney et al, 2010Mahaney et al, , 2011. The Raman spectra obtained on these mixed phases require careful interpretation, as this mixture produces a broad band between 1180 and 1450 D cm -1 centered at 1300 D cm -1 with a shoulder at 1345 D cm -1 , and a narrow band centered at 1575 D cm -1 (Fig.…”
Section: Marshall and Olcott Marshallmentioning
confidence: 99%
“…Laboratory impact experiments (e.g., Burchell et al 2001Burchell et al , 2006aBurchell et al , 2006b) are usually limited to relatively dense and competent projectiles, such as glass or metal beads and carefully sized mineral fragments, all mostly producing type A tracks. Experiments with fragments of hydrated minerals, e.g., lizardite (Burchell et al 2008) or compacted powders (Hörz et al 1998) produced bulbous (type B or C) tracks.…”
Section: Tracks In Stardust Aerogelmentioning
confidence: 99%